SEISMODYNAMICS AND DEEP INTERNAL ORIGIN OF THE NORTH CHINA ZONE OF STRONG EARTHQUAKES - Andrey A. Stepashko (Геодинамика и тектонофизика)
Space-and-time regularities of seismicity of the North China (Tan-Lu) zone are studies, and tectonic nature of strong earthquakes is analyzed. The concept of its genesis is still a matter of debate as this zone is located in the centre of the ancient SinoKorean craton, i.e. thousand kilometers away from convergent margins of Eurasia and the Pacific оcean and IndoAustralian plates (Figure 1). The information on the regional cycling dynamics [Xu, Deng, 1996] is updated. Two cycles, in which strong earthquakes (14 shocks with М≥7.0) occurred in the region under study, are distinguished, i.e. from 1500 to 1700, and from 1800 to 1980 (Figure 2). The seismodynamics of the North China zone is consistent with the Circum Pacific оcean deformation wave that occurs once in 300 years at the margin between Asia and the ocean and thus causes the strongest earthquakes (М≥8.8) and eruptions of volcanoes in the Pacific оcean belt [Vikulin et al., 2009, 2010]. This wave came to the northern regions of China in the years of 1500 and 1800 (Figure 3) and triggered seismic activity cycles. The second factor predetermining the seismicity of the Northern China is a specific structure of the region which can manifest seismic activity due to the impact of deformation waves. The genesis of the metastable structure of the region is related to tectonic restructuring of the lithosphere of the SinoKorean craton due to shear displacements in the Tan-Lu megazone. Regional variations of compositions of mantle xenoliths of the Sikhote Alin orogeny demonstrate that the latent strike of the Tan-Lu faults can be traced across the south-eastern areas of Russia to the Tatar Strait. These faults are borders of the Vshaped mantle block (400 x 1500 km) (Figure 5), which composition is characterized by an anomalous content of iron and a low depletion of peridotites. The tectonic mantle block maintains its activity; being impacted by compression from the west, it is squeezed out towards the Sakhalin Island and simultaneously subject to the clockwise rotation. As a result, along and above the margins of the covered lithospheric block in the southern Far East of Russia, main seismic zones have formed (Figure 5, B), wherein earthquakes of M≥5.0 are recorded. The anomalous mantle block at the base of the Sikhote Alin used to be a part of the SinoKorean craton; it was cut out in the JurassicCretaceous period and moved in the northeastern direction along the Tan-Lu shear fault. The lithosphere of the craton was significantly extended during closure of the remaining area, and an evident consequence of extension was formation of two Cenozoic rifting systems. In the Paleogene, the Hebei rift system occurred westward of the Tan-Lu megazone; it hosted earthquakes of the latest seismic cycle. The Shanxi rift system strikes in the northeastward direction and separates the western block of the craton (called Ordos) from the western block (called Hebei); it hosted earthquakes of the earlier seismic cycle.Recent geodynamics. During restructuring of the lithosphere, rotations of tectonic blocks were of importance, along with the lithospheric extension. The specific features of the craton structure suggest two tectonophysical mechanisms of rotation. Firstly, when the triangleshaped zone westward of Tan-Lu was being closed, the lithospheric segment rotated clockwise (Figure 5, С). Consequently, at the mobile front, a compression zone was formed; it has two maximums located NE and SW of the rotation centre. This structural pattern is typical of the lithosphere of the central part of the craton. Within the limits of two conjugated maximums westward of Tan-Lu, the crustal thickness is reduced, and the depth to the asthenosphere is sharply decreased (Figures 4, B and 4, C). The rotation of the blocks in the lithosphere resulted in formation of the gigantic anticline fold, where at the eastern area of rifting is located. Secondly, the clockwise rotation of the Hebei tectonic block triggered the counter clock rotation of the Ordos block that is located west of Hebei (Figure 6, A). At the border of the two blocks rotating in the opposite directions, grabens of the Sshaped Shanxi rift system were formed. The rotation of the tectonic blocks is evidenced by changes of strikes of ancient dykes of the craton (Figure 6, B). Regularities of migration of earthquakes in the North China zone reflect specific features of the tectonic structure of the craton (see Figure 4, А). The earthquakes of the latest cycle were caused by increasing compression of the lithospheric fold. The seismic events of the earlier cycle were associated with the rotation of the Hebei and Ordos blocks. The tectonic mechanism, that were triggered during restructuring of the lithosphere in the early Cretaceous – early Cenozoic, are still actively controlling seismicity in the North China zone.